Magmatic source and metamorphic grade of metavolcanic rocks from the Granjeno Schist: was northeastern Mexico a part of Pangaea?. (19th June 2015) - Torres Sánchez, Sonia Alejandra; Augustsson, Carita; Barboza Gudiño, José Rafael; Jenchen, Uwe; Ramírez Fernández, Juan Alonso; Abratis, Michael; Scherstén, Anders
Abstract: The geochemistry of the metavolcanic rocks from the Granjeno Schist in northeastern Mexico indicates an origin in different tectonic environments: mid‐ocean ridge and ocean island. High ratios of Hf/Th and Th/Nb (4.4–14 and 0.08–0.15), low ratios of LaN/YbN and LaN/SmN (0.74–1.7 and 0.60–1.4) and depleted LREE patterns in metabasalt display mid‐ocean ridge characteristics. In contrast, the pattern of trace‐element ratios and REEs in metabasalt and metapillow lava 60 km to the west indicates a magma source with ocean‐island basalt characteristics. Both areas were metamorphosed during the Late Carboniferous (300 ± 4 Ma). Estimated metamorphic conditions deduced from white mica and chlorite compositions, distinguish greenschist facies (350 °C and 4 kbar) for the mid‐ocean ridge basalt, and prehnite–pumpellyite facies (250 °C and 2.5 kbar) for the ocean‐island‐type basalt. This metamorphism took place at an active continental margin during Pennsylvanian time. Our new tectonic model, which differs from earlier models, suggests that the origin of the Granjeno Schist is related to a subduction zone located at the western margin of Pangaea, active after Laurentia–Gondwana collision. Copyright © 2015 John Wiley & Sons, Ltd.